Geochemical background and geopedological interactions of selenium in soils from Piauí state, Northeastern Brazil - Gustavo de Sousa de Oliveira Leite; Clístenes Williams Araújo do Nascimento; Rennan Cabral Nascimento; Cácio Luiz Boechat; Pâmalla Graziely Carvalho Morais; Paloma Cunha Saraiva; Lizandra de Sousa Luz Duarte; Jacqueline Sousa Paes Landim; Yuri Jacques Agra Bezerra da Silva (Revista Brasileira de Ciência do Solo, 2024)
ABSTRACT Although Selenium (Se) plays a role as a micronutrient for humans through vegetable consumption, it is also recognized as toxic when present in excessive quantities. Therefore, quantifying Se contents in soils can prevent diseases influenced by crop Se deficiency or excess. We aimed to measure background contents, establish quality reference values (QRV) for Se in soils from two Brazilian biomes (Cerrado and Caatinga), and assess how geopedological factors affect Se content and spatial variability. Two hundred and eight composite topsoil samples were analyzed for Se content, covering an area of about 251,578 km². Sampling sites were under the minimal anthropogenic influence to represent Se background contents. Selenium contents were determined by hydride generation atomic absorption spectroscopy (HGAAS), ranging from 0.002 to 4.78 mg kg-1. Most soils had contents below the world average of 0.44 mg kg-1 but still above the soil content that causes human Se deficiency (0.125 mg kg-1). Soils from Cerrado and Caatinga biomes showed similar average contents of Se, 0.41 and 0.47 mg kg-1, respectively. Organic carbon content and soil particle size (clay fraction) were the main factors governing Se content in the soils. Our results contribute to understanding the Se content and spatial distribution in tropical soils and the factors governing them. They also provide a tool for agriculture and environmental decision-makers to plan public policies regarding the management of Se levels in these and similar tropical soils in the world.